DESAIN LAPBOOK BERBASIS SETS BERBANTU MODEL KEMP MENINGKATKAN LITERASI BENCANA SISWA KELAS V SDN GADUNGAN 02 KABUPATEN BLITAR - Dwi Zakiatus Salamah; Cindya Alfi; Mohammad Fatih (Global Action and Education for Society, 2026)
This study addresses the low level of disaster literacy among elementary school students in disaster-prone regions of Indonesia, highlighting the need for innovative educational interventions. The research aims to develop and implement a lapbook-based learning media integrated with the SETS (Science, Environment, Technology, Society) approach and supported by the Kemp instructional design model to enhance disaster literacy for fifth-grade students at SDN Gadungan 02. Employing a research and development (R&D) methodology, the study follows the ASSURE model, encompassing stages such as learner analysis, objective setting, media selection, implementation, participation, and evaluation. Data were collected through expert validation, student and teacher questionnaires, and pretest-posttest assessments. The results indicate that the developed lapbook media is highly valid and feasible, with validation scores from material, media, and language experts exceeding 85%. Implementation of the lapbook led to a significant improvement in students’ disaster literacy, as evidenced by an increase in average test scores from 81% to 90%. The findings suggest that lapbook media, when designed using the SETS approach and Kemp model, effectively increases disaster literacy and student engagement. The study concludes that such media can serve as an effective tool for disaster education in elementary schools